Does Financial Distress Delay Financial Reporting? The Moderating Role of Corporate Governance in Property and Real Estate Firms - Anak Agung Putu Gede Bagus Arie Susandya; Anantawikrama Tungga Atmadja; I Made Pradana Adiputra; Desak Nyoman Sri Werastuti; Putu Sukma Kurniawan (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study examines whether financial distress delays financial reporting and whether corporate governance moderates this relationship in Indonesian listed property and real estate firms. Financial reporting delay (FRD) is measured using audit report lag, defined as the number of days between the fiscal year-end and the date of the independent auditor’s report. A higher FRD value indicates longer reporting delay and lower financial reporting timeliness. Financial distress is measured using a dummy variable based on the modified Altman Z-Score classification, while corporate governance is measured using a Corporate Governance Index based on ASEAN Corporate Governance Scorecard dimensions. Using 216 firm-year observations from Indonesian listed property and real estate companies during 2022–2024, the study applies moderated regression analysis. The findings show that financial distress has a positive and significant effect on FRD, indicating that distressed firms experience longer reporting delays. Corporate Governance Index has a negative and significant effect on FRD, suggesting that stronger governance reduces reporting delay. Moreover, the interaction between financial distress and corporate governance is negative and significant, indicating that corporate governance weakens the delay effect of financial distress. These findings highlight the importance of governance quality in maintaining timely audited reporting under financial pressure.